Evaluation & Comparison of the Efficiency of Ultrasonically Activated Intracanal Irrigants Grapeseed & Pineapple Extract in Removing the Smear Layer From the Apical Third of the Root Canal An in vitro sem analysis - Nikita Sebastian 20D05104; Dr Ashwini T S (JSS AHER, Mysuru JSSDCH, Mysuru, 2020)
01.Introduction 02.Aims & Objectives 03.Review of Literature 04.Methods & Materials 05.Results 06.Discussion 07.Conclusion 08.Limitations 09.Summary 10. References 11. Annexure